Are Fetal-Type Posterior Cerebral Arteries Associated With an Increased Risk of Posterior Communicating Artery Aneurysms?. Issue 6 (21st May 2018) - Thiarawat, Peeraphong; Jahromi, Behnam Rezai; Kozyrev, Danil A; Intarakhao, Patcharin; Teo, Mario K; Choque-Velasquez, Joham; Niemelä, Mika; Hernesniemi, Juha
Abstract: BACKGROUND: Fetal-type posterior cerebral arteries (F-PCAs) might result in alterations in hemodynamic flow patterns and may predispose an individual to an increased risk of posterior communicating artery aneurysms (PCoAAs). OBJECTIVE: To determine the association between PCoAAs and the presence of ipsilateral F-PCAs. METHODS: We retrospectively reviewed the radiographic findings from 185 patients harboring 199 PCoAAs that were treated at our institution between 2005 and 2015. Our study population consisted of 4 cohorts: (A) patients with 171 internal carotid arteries (ICAs) harboring unilateral PCoAAs; (B) 171 unaffected ICAs in the same patients from the first group; (C) 28 ICAs of 14 patients with bilateral PCoAAs; and (D) 180 ICAs of 90 patients with aneurysms in other locations. We then determined the presence of ipsilateral F-PCAs and recorded all aneurysm characteristics. RESULTS: Group A had the highest prevalence of F-PCAs (42%) compared to 19% in group B, 3% in group C, and 14% in group D (odds ratio A : B = 3.041; A : C = 19.626; and A : D = 4.308; P < .001). PCoAAs were associated with larger diameters of the posterior communicating arteries (median value 1.05 vs 0.86 mm; P = .001). The presence of F-PCAs was associated with larger sizes of the aneurysm necks (median value 3.3 vs 3.0 mm; P = .02). CONCLUSION: PCoAAs were associated with a higher prevalence of ipsilateral F-PCAs. This variant was associated with larger sizes of the aneurysm necks but was not associated with the sizes of the aneurysm domes or with their rupture statuses.